(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2024)
This study aimed at identifying Dialogue Values included in the topics of Reading of Arabic Language Textbooks for the 7th, 8th, and 9th grades of the basic education stage in Libya. To achieve this, the researcher prepared alist of dialogue values, with (22) values, and Content Analysis Card based on this list. The study sample and its population consisted of all topics of reading in the Arabic Language Textbooks. After the end of content analysis, the results showed that the degree of availability of dialogue values in the textbooks of the combined three grades was in a medium limit, and the reptitions and rates were: "the 7th, 321, with 32.856%, the 8th, 336, with 34.391%, and the 9th,320, with 32.753%" out of the total repetitions of (977). And the results revealed that the value of " Estimation of the situation " came first; it was repeated (109) times, with a rate of (11.156%), while the reptitions of the other values varied near and far from it. In the light of these results, the study made some recommendations.